2019
DOI: 10.1016/j.msard.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome-based signature of disease pathology in MS

Abstract: Background-Diagnostic delays are common for multiple sclerosis (MS) since diagnosis typically depends on the presentation of nonspecific clinical symptoms together with radiologically-determined central nervous system (CNS) lesions. It is important to reduce diagnostic delays as earlier initiation of disease modifying therapies mitigates long-term disability. Developing a metabolomic blood-based MS biomarker is attractive, but prior efforts have largely focused on specific subsets of metabolite classes or anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 58 publications
2
34
0
1
Order By: Relevance
“…Random forests, an ensemble learning method, were used to identify lipids relevant for disease/gender classification. Similar to a previous study [41], the classification at each node in a tree was done with 100 randomly selected metabolites and the forest consisted of 5000 trees. The process was repeated 50 times, and the model with the highest area under the curve (AUC) was kept.…”
Section: Experimental Design and Statistical Analysesmentioning
confidence: 99%
“…Random forests, an ensemble learning method, were used to identify lipids relevant for disease/gender classification. Similar to a previous study [41], the classification at each node in a tree was done with 100 randomly selected metabolites and the forest consisted of 5000 trees. The process was repeated 50 times, and the model with the highest area under the curve (AUC) was kept.…”
Section: Experimental Design and Statistical Analysesmentioning
confidence: 99%
“…Pyroglutamate, laurate, N-methylmaleimide, acylcarnitine C14:1, and phosphatidylcholine were among these metabolites. The authors also found metabolites involved in biological pathways like glutathione metabolism, cellular membrane composition, FA metabolism, and oxidation [ 109 ].…”
Section: Metabolites In Specific Neurological Diseasesmentioning
confidence: 99%
“…Many studies have already demonstrated the importance of some phospholipids such as lysophosphatidylethanolamine and sphingomyelin to assess the degree of neuronal damage and changes in the myelin sheath potential predictors of the stage of diseases such as AD, PD, and MuS [ 70 , 109 , 111 ]. In addition, it is also possible to observe the involvement of harmful oxidative processes, with the potential to affect membranes, as has already been proposed for Lysophosphatidic acid C18: 2 in patients with AD [ 71 ].…”
Section: Metabolites In Specific Neurological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…As metabolites are the biological end products of upstream processes involving gene and protein expression, the metabolome closely reflects the clinical phenotype and, thus, can provide valuable insight in to underlying pathological processes and identify novel biomarkers of disease. The majority of metabolomics studies in MS focus on the identification of blood-borne metabolite perturbations in MS patients relative to healthy controls using both nuclear magnetic resonance (NMR)-based [6][7][8] and mass spectrometry-based metabolomics [9][10][11][12] . While this is useful in aiding our understanding of MS disease activity as a whole, the distinction between MS and controls is not a clinical diagnostic challenge.…”
mentioning
confidence: 99%